Influence of pectin on phenylpropanoid accumulation in buckwheat (Fagopyrum esculentum) sprout - Park, Chang Ha; Yeo, Hyeon Ji; Choi, Minsol; Sathasivam, Ramaraj; Uddin, Md. Romij; Muthuraman, Meenakshi Sundaram; Kim, Haenghoon; Park, Sang Un (Journal of Phytology, 2023)
Buckwheat (Fagopyrum esculentum Monech) contains several secondary metabolites like phenolic chemicals. Pectin has been demonstrated to be an efficient elicitor from the biotic group for triggering the defensive response, which enhances the production of secondary metabolites. In this study, the effect of pectin on the growth of buckwheat sprouts and the production of phenylpropanoid compounds in common buckwheat sprouts was investigated by using high-performance liquid chromatography (HPLC). Pectin treatments of 0, 2, 4, 6, and 8 mg/L were administered on buckwheat sprouts for ten days to assess the growth characteristics and optimum concentrations. In comparison to the control treatment, 2 mg/L pectin enhances the shoot length by 24%. But when pectin concentration continued to rise, a tendency toward shorter shoots was seen. Pectin treatment decreased the fresh weight of the sprout as compared to the control treatment. The phenylpropanoid accumulation in buckwheat sprouts varied depending on the amount of pectin utilized. Pectin treatment at 6 mg/L resulted in a 15.10% increase in total phenylpropanoid accumulation. The findings of this study indicate that pectin is a possible elicitor, however, more research on how pectin affects the buildup of phenylpropanoids in buckwheat sprouts would be more intriguing to examine the implications of this work.